Host suitability for germination differs from that of later stages of development in a rare epiphytic orchid - González Orellana, Normandie; Salazar Mendoza, Aragne; Tremblay, Raymond L.; Ackerman, James D. 1950- (2024)
We explore phorophyte suitability for germination and establishment of the epiphytic orchid, Psychilis kraenzlinii. We found that the orchid grows on a subset of the available tree species and shows preference for the endemic Machaonia portoricensis (Rubiaceae). The orchid preferred trees with smoother bark, high water holding capacity and low water retention capacity. Microclimatic conditions under which embryos began pre-germination stages mirrored that of the adult orchid, but germination did not, suggesting that suit-able germination sites are not necessarily the best sites for later stages of development.
Exploramos la utilización de árboles y los patrones de germinación de la orquídea epífita, Psychilis kraenzlinii. Encontramos que P. kraenzlinii crece en un subconjunto de las especies de árboles disponibles y muestra preferencia por la endémica Machaonia portoricensis. La orquídea prefiere árboles con corteza lisa y alta capacidad de sostener agua y baja capacidad de retención de agua. Las condiciones microclimáticas bajo las cuáles los embriones empienzan etapas pre-germinacíon, reflejan los de la orquídea adulta, pero las condiciones bajo las cuáles los embriones llegan a etapas de germinación no. Lo que sugiere que los sitios de germinación adecuados no son necesariamente los lugares donde mejor se producirá el desarrollo a etapas más avanzadas de la germinación.
Keywords: ORQUIDEAS -- INVESTIGACIONES; GERMINACION; EPIFITAS; SEMILLAS